Differential response of plants to aluminum. a review (2012)
Aluminum toxicity is a major limiting factor to the growth and development of plants in acidic soils worldwide, occurring in 40% of arable soils. The root seems to be the object of aluminum toxicity, particularly the apex, producing a rapid inhibition of cell division and elongation of the root. Fortunately, plants differ in their ability to tolerate aluminum and grow in acidic soils. Tolerance mechanisms have commonly been defined in genetic and physiological terms, however, tolerance mechanisms are not the same in all species, moreover, in certain species, mechanisms can operate simultaneously producing tolerance through their combined effects; the genetic control of tolerance can be very complex and involve many genes. The toxic action of aluminum, according to several studies, can be reduced by internal or external Al chelation with different organic compounds such as organic acids, proteins and polysaccharides, although this type of tolerance mechanism is very controversial and highly debated.